1999
DOI: 10.1016/s0896-6273(00)81096-x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Membrane Potential Fluctuations in Neurons of the Cat Visual Cortex

Abstract: We have recorded intracellularly from pairs of neurons less than 500 microm distant from one another in V1 of anesthetized cats. Cross-correlation of spontaneous fluctuations in membrane potential revealed significant correlations between the cells in each pair. This synchronization was not dependent on the occurrence of action potentials, indicating that it was not caused by mutual interconnections. The cells were synchronized continuously rather than for brief epochs. Much weaker correlations were found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
344
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(383 citation statements)
references
References 62 publications
36
344
2
1
Order By: Relevance
“…This dynamic, which has similar characteristics to the slow oscillation discussed above, depends on synaptic activity and intrinsic currents, but does not have a clear periodicity and is limited to small ensembles of cells (Mao et al, 2001;Cossart et al, 2003). Fluctuation of finite network patterns, similar to the spontaneous events, is also evoked by sensory stimulation in deeply anesthetized animals (Lampl et al, 1999;Tsodyks et al, 1999;Arieli et al, 1996;Anderson et al, 2000;Leopold et al, 2003;Petersen et al, 2003). Thus, the population dynamics of cortical networks might display a random walk between synchronous UP states in subpopulations of neurons, which seem to reflect behaviorally activated states and silence (Kenet et al, 2003).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 88%
“…This dynamic, which has similar characteristics to the slow oscillation discussed above, depends on synaptic activity and intrinsic currents, but does not have a clear periodicity and is limited to small ensembles of cells (Mao et al, 2001;Cossart et al, 2003). Fluctuation of finite network patterns, similar to the spontaneous events, is also evoked by sensory stimulation in deeply anesthetized animals (Lampl et al, 1999;Tsodyks et al, 1999;Arieli et al, 1996;Anderson et al, 2000;Leopold et al, 2003;Petersen et al, 2003). Thus, the population dynamics of cortical networks might display a random walk between synchronous UP states in subpopulations of neurons, which seem to reflect behaviorally activated states and silence (Kenet et al, 2003).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 88%
“…In vivo, the LFP correlates with synchronized activity of local neuronal populations (Arieli, 1992;Lampl, Reichova et al, 1999). LFPs also contain more information than isolated spikes about a network state, e.g.…”
Section: Nlfp Clusters Reflect Precise Spatiotemporal Patterns Of Synmentioning
confidence: 99%
“…successive initiation at different sites ('waves') (Crain, 1966;Calvet, 1974;Dichter, 1978;Plenz and Aertsen, 1996a;Plenz and Aertsen, 1996b;Gorba, Klostermann et al, 1999;Klostermann and Wahle, 1999;Corner, van Pelt et al, 2002;Eytan and Marom, 2006). Using extracellular local field potentials (LFP), which are particularly well suited to study network states as they correlate with synchronized activity of local neuronal populations in vivo (Arieli, 1992;Lampl, Reichova et al, 1999), we demonstrated recently that the spontaneous LFPs in isolated cortical networks are ordered such that the probability P of a spatiotemporal LFP cluster of size s follows a power law…”
Section: Introductionmentioning
confidence: 99%
“…Large, persistent changes in membrane potential can also occur in a response to behavioral state changes , or sensory stimulation (Anderson et al, 2000;Carandini and Ferster, 1997). Up and down states have been observed in frontal cortical areas (Lewis and O'Donnell, 2000;Léger et al, 2005), somatosensory (Sachdev et al, 2004;Steriade et al, 2001), visual (Lampl et al, 1999), olfactory areas (Luo and Katz, 2001;Margrie and Schaefer, 2003), striatum (Stern et al, 1997;Wilson and Kawaguchi, 1996), and many others.…”
mentioning
confidence: 99%
“…Various studies suggested the involvement of intracortical mechanisms (Steriade et al, 1993b), intrinsic network properties (Lampl et al, 1999;McCormick et al, 2003), pairwise correlations among neuronal inputs (Benucci et al, 2004), or activity-dependent synaptic depression among excitatory neurons (Holcman and Tsodyks, 2006).…”
mentioning
confidence: 99%